Influences of Internal Service Quality, Employee Satisfaction, External Service Satisfaction And Customer Satisfaction Toward Customer Loyalty Of Gojek Service Users in Malang - Muhammad Rudijav Andalas (IPTEK Journal of Proceedings Series, 2020)
This research aims to examine and analyze internal service quality influences toward external service quality and employee satisfaction; to examine and analyze employee satisfaction influences toward external service quality and customer satisfaction; to examine and analyze external service quality toward customer satisfaction; and to examine and analyze customer satisfaction influences toward customer loyalty of Gojek service users in Malang. The research type used is Explanatory Research. The investigation type in this research is determining causal relation. The population consists of samples of 150 employees [driver] and Gojek customers in Malang. The technique of taking samples in this research is using purposive sampling. The analysis technique used in this research is SEM operated through AMOS 18. From the analysis results, it can be concluded that internal service quality has influences toward external service quality and employee satisfaction by the values of CR as respectively 2.794 and 5.436 and also p-value smaller than 0.05. Employee satisfaction does not have influences toward external service quality by the value of CR as 0.908 and p-value bigger than 0.05, but employee satisfaction has influences toward customer satisfaction by CR as 2.029 amd p-value smaller than 0.05. External service quality has influences toward customer satisfaction by CR as 2.739 and p-value smaller than 0.05. Then, customer satisfaction has influences toward service user loyalty by CR as 4.451 and p-value smaller than 0.05. Conclusions is Internal Service Quality has influences toward External Service Quality of Gojek service users in Malang, Internal Service Quality has influences toward Employee Satisfaction of Gojek service users in Malang, Employee Satisfaction does not have influences toward External Service Quality of Gojek service users in Malang, Employee Satisfaction has influences toward Customer Satisfaction of Gojek service users in Malang, External Service Quality has influences toward Customer Satisfaction of Gojek service users in Malang, Customer Satisfaction has influences toward Loyalty of Gojek service users in Malang.